AmpliSeq Screening of Genes Encoding the C-Type Lectin Receptors and Their Signaling Components Reveals a Common Variant in MASP1 Associated with Pulmonary Tuberculosis in an Indian Population - Klassert, Tilman E.; Goyal, Surabhi; Stock, Magdalena; Driesch, Dominik; Hussain, Abid; Berrocal-Almanza, Luis Carlos; Myakala, Rajashekar; Sumanlatha, Gaddam; Valluri, Vijayalakshmi; Ahmed, Niyaz; Schumann, Ralf R.; Flores, Carlos; et al. (Frontiers in Immunology, 2018)
Tuberculosis (TB) is a multifactorial disease governed by bacterial, host and environmental factors. On the host side, growing evidence shows the crucial role that genetic variants play in the susceptibility to Mycobacterium tuberculosis (Mtb) infection. Such polymorphisms have been described in genes encoding for different cytokines and pattern recognition receptors (PRR), including numerous Toll-like receptors (TLRs). In recent years, several members of the C-type lectin receptors (CTLRs) have been identified as key PRRs in TB pathogenesis. Nevertheless, studies to date have only addressed particular genetic polymorphisms in these receptors or their0 related pathways in relation with TB. In the present study, we screened the main CTLR gene clusters as well as CTLR pathway-related genes for genetic variation associated with pulmonary tuberculosis (PTB). This case-control study comprised 144 newly diagnosed pulmonary TB patients and 181 healthy controls recruited at Bhagwan Mahavir Medical Research Center (BMMRC), Hyderabad, India. A two-stage study was employed in which an explorative AmpliSeq-based screening was followed by a validation phase using iPLEX MassARRAY. Our results revealed one SNP (rs3774275) in MASP1 significantly associated with PTB in our population (joint analysis p = 0.0028). Furthermore, serum levels of MASP1 were significantly elevated in TB patients when compared to healthy controls. Moreover, in the present study we could observe an impact of increased MASP1 levels on the lectin pathway complement activity in vitro. In conclusion, our results demonstrate a significant association of MASP1 polymorphism rs3774275 and MASP1 serum levels with the development of pulmonary TB. The present work contributes to our understanding of host-Mtb interaction and reinforces the critical significance of mannose binding-lectin and the lectin-complement pathway in Mtb pathogenesis. Moreover, it proposes a MASP1 polymorphism as a potential genetic marker for TB resistance.